A study on the effects of EEG and ECG signals while listening to Qur'an recitation - Alshaikhli, Imad Fakhri Taha; Yahya, Sabaa Ahmed; Pammusu, Irma; Alarabi, Khamis Faraj (Institute of Electrical and Electronics Engineers Inc., 2014)
The brain performs many important functions, and for this reason have been the subject of much research. Electroencephalograms (EEG) and Electrocardiograms (ECG) are techniques used to record electrical activity in the brain and heart respectively. This research was conducted to compare the effect on EEG and ECG temporal signals while listening to Quran recitation and listening to music. The EEG and ECG signals were captured from three subjects in a special environment. Data analysis was conducted for the EEG signal in the frequency domain, while the ECG signal was analyzed in the time domain. It was concluded that the subjects were more relaxed while listening to Quran recitation.